Debt Maturity and Investor Heterogeneity - Darst, Matthew; Refayet, Ehraz (Journal of Financial and Quantitative Analysis, 2025)
AbstractThis paper studies how investor heterogeneity impacts equilibrium debt maturity. The optimal issuance strategy combines long- and short-term debts. A long-term debt contains default risk but hedges against intermediate downturns. A short-term debt provides repayment commitment but requires being rolled over and becomes risky during downturns. Issuing multiple debt maturities spreads the cost of these risky claims to investors most willing to hold risk at different points in time. The model predicts that debt maturity is more dispersed with lower financing costs and more investment opportunities when debt ownership is spread among many different types of investors.